Noise-resistant and mechanically strong Rogowski coils used to measure parameters of high-current pulses with nanosecond front - Gerasimov, A.I. (Вопросы атомной науки и техники, 2004)
There are presented the characteristics of two versions of Rogowski coils with single- or multi-layer coil wound
with a screened wire and with the toroidal core made of metal. Приведено характеристики двох варіантів поясів Роговського c одно- або багатошаровою котушкою,
намотаною екранованим проводом, і з тороїдальним осердям з металу. Приведены характеристики двух вариантов поясов Роговского c одно- или многослойной катушкой, намотанной экранированным проводом, и с тороидальным сердечником из металла.